LATAR BELAKANG PEMILIHAN PENGOBATAN TRADISIONAL PADA MASYARAKAT DI DESA RANTAU PANJANG KIRI HILIR KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Mulyanti "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study on "Background Selection Of Traditional Treatment On The Community In The Village Of Long Left Rantau Downstream District Kubu Babussalam Rokan HilirDistrict".Where the study was intended to explain how the implementation of traditional medicine by community village of long left rantau downstreamand what are the factors that influence the conduct of traditional medicine.Subjects in this study is that people go to traditional healers / traditional inthe village of long left rantau downstream.In this study the author uses qualitative research is research that produces descriptive data in the form of words written or oral, and explain the data through logical reasoning to draw conclusions on the terms of the logic and the data analyzed,so that it can systematically describe the situation in accordance with the phenomenon being studied.Data collection technique used interview, observation, documentation.Based on the results of this research community in The Village Of Long Left Rantau Downstream still use traditional medicine until now,they even believe in traditional medicine because they had been receiving treatment from the ancestors of the first to get it now.Every medication they are taking action to do to go to traditional healers or medicine, because they put the two treatments to medical and traditional.Keywords: Traditional, Medicine, The Village Of Long Left Rantau Downstream